Functional behaviour and microscopic analysis of ammonium sensors subject to fouling in activated sludge processes. Issue 10 (21st July 2020) - Cecconi, Francesca; Reifsnyder, Samuel; Sobhani, Reza; Cisquella-Serra, Albert; Madou, Marc; Rosso, Diego
Abstract : ISE-ammonium sensors subject to fouling display an increase in response time and an inexorable degradation of the measurement accuracy. The fouling morphology and composition were also studied by EDX analysis. Abstract : Fouling is an issue associated with all sensor instrumentation deployed in wastewater that causes a loss in sensitivity and reproducibility of the sensor elements, thus requiring frequent re-calibration. This paper presents a comprehensive analysis of the fouling development in activated sludge processes with a case study on ammonium sensor and ion-selective electrode technology. The response time of the electrodes is found to be the most impacted by fouling. By analysing step-change experiments with a diffusion model, after one week of fouling the response time is demonstrated to increase exponentially with time. The performance of the sensor is also affected in terms of measurement accuracy, showing a negative drift of the fouled sensor (−0.11 mg NH4 + l −1 d −1 ). Scanning electron microscopy analysis and energy dispersive X-ray spectroscopy elemental mapping were performed over new and used sensor membranes to study the irreversible fouling composition and morphology. Fouling appears as a thick coating with different agglomerates and crevasses, which reveal damage on the PTFE protective layer of the membrane. Fe, P, Ca, Mn, S, K and Cl were the main elements detected, in decreasing order. The high content of Fe in the fouling layer originates from the addition of ferric salts to the primary treatment of the plant, which becomes a major contributor to the inorganic fouling of the sensor. This study also quantifies the increase in total suspended solids (TSS), volatile suspended solids (VSS), and total Fe in the reversible fouling layer over time as described using a saturation model. However, the relative composition remains stable: 84% for VSS/TSS and 20% for Fe/iSS, on average.